Post-production modifications of murine mesenchymal stem cell (mMSC) derived extracellular vesicles (EVs) and impact on their cellular interaction. (February 2020) - Le Saux, Sarah; Aarrass, Hanna; Lai-Kee-Him, Joséphine; Bron, Patrick; Armengaud, Jean; Miotello, Guylaine; Bertrand-Michel, Justine; Dubois, Emeric; George, Simon; Faklaris, Orestis; Devoisselle, Jean-Marie; Legrand, Philippe; et al.
Abstract: In regards to their key role in intercellular communication, extracellular vesicles (EVs) have a strong potential as bio-inspired drug delivery systems (DDS). With the aim of circumventing some of their well-known issues (production yield, drug loading yield, pharmacokinetics), we specifically focused on switching the biological vision of these entities to a more physico-chemical one, and to consider and fine-tune EVs as synthetic vectors. To allow a rational use, we first performed a full physico-chemical (size, concentration, surface charge, cryoTEM), biochemical (western blot, proteomics, lipidomics, transcriptomics) and biological (cell internalisation) characterisation of murine mesenchymal stem cell (mMSC)-derived EVs. A stability study based on evaluating the colloidal behaviour of obtained vesicles was performed in order to identify optimal storage conditions. We evidenced the interest of using EVs instead of liposomes, in regards to target cell internalisation efficiency. EVs were shown to be internalised through a caveolae and cholesterol-dependent pathway, following a different endocytic route than liposomes. Then, we characterised the effect of physical methods scarcely investigated with EVs (extrusion through 50 nm membranes, freeze-drying, sonication) on EV size, concentration, structure and cell internalisation properties. Our extensive characterisation of the effect of these physical processes highlights their promise as loading methods to make EVs efficient delivery vehicles.